Use of a Point-of-Care Progesterone Assay to Predict Onset of Parturition in the Bitch - Nöthling, Johan O.; Joonè, Carolynne J.; Hegarty, Evan; Schooley, Elizabeth K.; De Cramer, Kurt G. M. (Frontiers in Veterinary Science, 2022)
Assay of circulating progesterone (P4) is commonly used to estimate progress through late gestation in the bitch. Point-of-care assays provide rapid results, a major advantage over laboratory-based assays. The aims of this study were to compare P4 levels determined by the Catalyst® Progesterone point-of-care assay with those determined by chemiluminescent immunoassay (CLIA) and to identify the expected distribution of Catalyst P4 levels at time intervals within three days prior to the onset of parturition in pregnant bitches. Twenty-eight pregnant bitches carrying two or more fetuses were admitted to a specialist veterinary reproduction hospital 53 days after the onset of cytological diestrus or, when that date was not known, 57 days after the last mating. Vaginal speculum examinations were performed every 6 hours until the onset of cervical dilatation (TCD). Serum samples were collected twice daily (08h00 and 18h00) until TCD. For most samples, fresh serum was assayed for P4 immediately using the Catalyst assay (CatP4), then frozen until assayed by CLIA (IMMULITE 2000; ImmP4). However, for some samples, CatP4 was not analysed prior to freezing. For these data points (n = 33), CatP4 for fresh serum was estimated from CatP4 assayed on frozen-thawed serum, based on a comparison between CatP4 on fresh versus frozen-thawed sera. In comparison to ImmP4, CatP4 levels up to and including 7 nmol/L appear to have a constant bias of -1.69 nmol/L (limits of agreement -4.91 to 1.52), while levels greater than 7 nmol/L appear to have a proportional bias of -17.9% (limits of agreement -68.6% to 32.7%). Bootstrapped percentiles of CatP4 results spanned 0.4–9 nmol/L within 12 h of TCD, 0.9–11 nmol/L 12–24 h from TCD and 2.2–13.5 nmol/L 24–36 h from TCD. A CatP4 greater than 9 nmol/L indicates a bitch is unlikely to reach TCD within 12 hours. Bitches with CatP4s below 3.5 nmol/L are likely to reach TCD within 36 hours and bitches with a CatP4 below 2.2 nmol/L are likely to reach TCD within 24 hours. In conclusion, the Catalyst Progesterone assay provides rapid assessment of circulating P4 in the bitch, with clinical application in the monitoring of preparturient bitches.